2005
DOI: 10.1002/jcla.20082
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Cardiac Troponin T and D-Dimer in the Evaluation of Myocardial Damage

Abstract: Acute myocardial infarction (AMI) disrupts cardiac cell membranes, releasing intracellular cardiac proteins into the vascular system. Some of these proteins, including the cardiac troponin subunits T and I, have proven useful for diagnosing myocardial damage. Intracoronary thrombosis plays a key role in the pathogenesis of AMI, and the formation of an occlusive thrombus usually precedes the development of myocardial damage. To evaluate whether there is an association between the size of intracoronary thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…D-dimer was lower in patients with cardiac troponin T < 0.01 ng/ml than those with cardiac troponin T > 0.01 ng/ml. No correlation was found between D-dimer and cardiac troponin T levels in patients with cardiac troponin T > 0.01 ng/ml [1].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…D-dimer was lower in patients with cardiac troponin T < 0.01 ng/ml than those with cardiac troponin T > 0.01 ng/ml. No correlation was found between D-dimer and cardiac troponin T levels in patients with cardiac troponin T > 0.01 ng/ml [1].…”
Section: Discussionmentioning
confidence: 77%
“…In the event of myocardial damage secondary to acute myocardial ischemia, intracellular cardiac proteins and enzymes are released into the circulation via cardiac cell membranes [1,2]. Patients with postinfarction myocardial rupture, a severe complication of acute myocardial infarction, often develop rapid hemodynamic deterioration [3], and are usually associated with more extensive myocardial damage [4], the assessment of which has not been fully conducted in a way similar to that of the myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The serum D-dimer has also been found to be increased in patients with ACS, although sensitivity has been found to be poor when specificity is reasonable. Derhaschnig found a sensitivity of only 18% when the specificity was 92% (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Although increases in crosslinked fibrin degradation products were not sensitive enough for the diagnosis, they appear to predict those patients who are at higher risk for AMI-related complications [12]. Moresco et al observed that D-dimer levels are lower in patients with cTnT < 0.01 lg/l than in patients presenting cTnT > 0.01 lg/l, though D-dimer results are not associated with the levels of cTnT in patients with cTnT > 0.01 lg/l [13]. In a study on consecutive patients admitted to the coronary unit for evolving ACS within 6 h from the onset of infarct-related symptoms, D-dimer had a poor early sensitivity [14].…”
Section: Discussionmentioning
confidence: 99%